Reactive diving and sprinting performances in soccer goalkeepers improved by caffeine consumption and post-activation performance enhancement - Impey, J.; Bahdur, K.; Kramer, M. (German Journal of Exercise and Sport Research, 2022)
Decisive moments in field-sports such as soccer are dictated by the number of saves by the goalkeeper, which involves reactive diving and jumping actions. The purpose of this study was to evaluate whether caffeine and post-activation performance enhancement (PAPE) could elicit meaningful changes in reactive sprinting and diving times in goalkeepers. Twenty-five goalkeepers (soccer; n = 25) participated in the study (age: 21.68 ± 2.21 years; height: 1.74 ± 0.05 m; weight: 74.30 ± 11.71 kg; playing experience: 8.48 ± 4.05 years). Goalkeepers completed a series of tests assessing simple and complex reaction/movement times for various treatments. Within-group differences were present for the treatments, showing that reactive sprinting and diving times were enhanced by 5.17 and 14.34%, respectively, under caffeine consumption, and by 4.25 and 13.60%, respectively, under plyometric conditions. Caffeine and plyometric trials were not significantly different for sprinting (Mdiff = 0.013 s, p = 0.817) and diving (Mdiff = 0.000 s, p = 0.999), respectively. Performance improvements may likely be related to increased information processing speed and/or enhanced lower extremity force production.